The Belt and Road Initiative at Ten From Macro, Financial and Industrial Trends - CICC Research, CICC Global Institute; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book analyzes the achievements and challenges of the Belt and Road Initiative (BRI) from the macro and industrial, real and financial, domestic and international perspectives, and explores the opportunities for future development and related public policy issues. It is a new research achievement of CICC Research and CICC Global Institute on major issues in China$1 (Bs new development stage. The year 2023 marks the tenth anniversary of the Belt and Road Initiative (BRI). Over the past decade, BRI has established more than 3,000 cooperation projects, galvanized nearly 1 trillion U.S. dollars of investment, created more than 420,000 jobs, and lifted nearly 40 million people out of poverty. BRI has made remarkable achievements in promoting connectivity and cooperative development between China and participating countries, and has been welcomed by the international community both as a public good and a cooperation platform. Compared with ten years ago, the global environment has undergone profound changes. COVID-19 epidemic has brought great impacts to the world, and the post-epidemic economic recovery is uneven, with some long-term scarring effects still emerging. New changes and constraints, such as geopolitical events, industry chain adjustment, and green transition, have also exerted far-reaching influences on the economic fundamentals and global governance. Under the new situation, international cooperation mechanisms, including BRI, are facing new problems and challenges, which need to be explored and solved in practice. This book is both academically rigorous and readable, and provides valuable references for public policy departments, enterprises, and financial institutions who seek to better understand the macro, financial and industrial trends of BRI.s
Development is key to advancing the Belt and Road Initiative -- Establishing an open and sustainable Belt and Road innovation system -- Working together towards a green transition -- Promoting financial cooperation among BRI countries -- BRI finance: Important roles of the capital market.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: International economic relations; Macroeconomics; Finance, Public; International Economics; Macroeconomics and Monetary Economics; Public Economics